2021
DOI: 10.1002/ijop.12776
|View full text |Cite
|
Sign up to set email alerts
|

Political identities of Chinese international students: Patterns and change in transnational space

Abstract: Amid the ongoing international tensions surrounding China, Chinese international students (CISs) in Western countries have become targets of political suspicion. Against discriminatory voices that make sweeping generalisations about CISs, this research argues that their political identities are in fact diverse and malleable. Using theories of postmodernism and transnationalism, this study applies thematic analysis and discourse analysis to interviews with 28 CISs, yielding four major findings. First, it identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This reductionism precludes multiple perspectives and paves the way for binary thinking (W. Liu, 2020). The aforementioned Chinese media campaigns, for example, depicted a powerful, committed Chinese nation-state that was ready to support its overseas citizens against a precarious, racist western society (Gao, 2022a). Meanwhile, on the US side, there have been vociferous right-wing voices calling China out for its allegedly Communist opposition to democracy, sidestepping the fact that China's neoliberal capitalism shares much common ground with US right-wing politics.…”
Section: Polarizing Geopolitics: the Binary Logic Of Double Unbelongingmentioning
confidence: 99%
See 3 more Smart Citations
“…This reductionism precludes multiple perspectives and paves the way for binary thinking (W. Liu, 2020). The aforementioned Chinese media campaigns, for example, depicted a powerful, committed Chinese nation-state that was ready to support its overseas citizens against a precarious, racist western society (Gao, 2022a). Meanwhile, on the US side, there have been vociferous right-wing voices calling China out for its allegedly Communist opposition to democracy, sidestepping the fact that China's neoliberal capitalism shares much common ground with US right-wing politics.…”
Section: Polarizing Geopolitics: the Binary Logic Of Double Unbelongingmentioning
confidence: 99%
“…In my fieldwork, I have similarly found that upper-class Chinese immigrants are more capable of fending off the impact of the China–West confrontation. It is the underprivileged who weather the brunt of it (Gao, 2022a). In one extreme case, one of my participants was unable to afford the soaring price of a flight ticket and, as a result, had to watch her well-off peers returning to China one by one while she herself remained stranded in the UK with an expired visa for nearly six months.…”
Section: From Positivism To Social Constructionism: the Politics Of B...mentioning
confidence: 99%
See 2 more Smart Citations
“…Using theme and discourse analysis, Gao, Z. selected 28 Chinese citizens for survey interviews and identified three modes of political identity in China at this stage. It is concluded from the above political identity that the citizens' political identity comes from their socioeconomic status, and the application of the research strategy in education and decision-making can enhance the citizens' political identity [15]. Liang, L. analyzes the current situation of Civic and Political Education in colleges and universities from the perspective of Civic and Political Education.…”
Section: Introductionmentioning
confidence: 99%